Técnica Delphi no processo de validação do Questionário de Avaliação da Atenção Básica (QualiAB) para aplicação nacional1 - Zarili, Thais Fernanda Tortorelli [UNESP]; Castanheira, Elen Rose Lodeiro [UNESP]; Nunes, Luceime Olivia [UNESP]; Sanine, Patrícia Rodrigues [UNESP]; Carrapato, Josiane Fernandes Lozigia; Machado, Dinair Ferreira [UNESP]; Ramos, Nádia Placideli [UNESP]; Mendonça, Carolina Siqueira [UNESP]; Nasser, Mariana Arantes; Andrade, Marta Campagnoni; Nemes, Maria Ines Battistella (Faculdade de Saúde Pública, Universidade de São Paulo. Associação Paulista de Saúde Pública., 2021)
This article aims to describe the use of the Delphi Technique in a process of updating and validating the content of the Primary Care Services Quality Assessment Questionnaire (QualiAB) for national application. In this study, 19 experts with experience in research in health evaluation, care and management in Primary Health Care (PHC) agreed to participate. A revised version of the QualiAB instrument with 105 indicators was submitted for evaluation as to its relevance, national applicability and acceptability. The modified Delphi Technique was performed in two rounds. The response rate of experts in the first round was 73.6%, 40 indicators were accepted and 65 did not reach consensus, of which 54 obtained suggestions to change the question and/or indicator. In the second, the response rate was 92.8%, and 65 indicators were resent with incorporation of changes, of which six were accepted. Of the remaining 59, 51 obtained suggestions for change. The modified Delphi Technique contributed to the improvement of the QualiAB instrument as an intermediate step in an iterative validation process. However, the performance in two rounds proved to be insufficient to validate the organizational quality indicators in view of the scope and diversity of the actions performed by the PHC services.

Este trabalho tem como objetivo descrever o uso da Técnica Delphi no processo de atualização e validação de conteúdo do Questionário de Avaliação da Qualidade de Serviços de Atenção Básica (QualiAB) para aplicação nacional. Deste estudo participaram 19 especialistas com experiência em pesquisa em avaliação em saúde, assistência e gestão em atenção primária à saúde (APS). Uma versão revisada do instrumento QualiAB com 105 indicadores foi encaminhada para avaliação quanto ao grau de relevância, aplicabilidade nacional e aceitabilidade. A Técnica Delphi modificada foi realizada em duas rodadas. Os resultados apontam que a taxa de resposta na primeira rodada foi de 73,6%, 40 indicadores foram aceitos e 65 não obtiveram consenso, dos quais 54 receberam sugestões de alteração da questão e/ou do indicador. Na segunda rodada a taxa de resposta foi de 92,8%. Foram reenviados 65 indicadores com incorporação de alterações, dos quais seis foram aceitos. Dos 59 restantes, 51 obtiveram sugestões de alteração. A Técnica Delphi modificada contribuiu para o aprimoramento do instrumento QualiAB enquanto etapa intermediária de um processo de validação iterativa. Contudo, a realização em duas rodadas demonstrou ser insuficiente para validação dos indicadores de qualidade organizacional diante da abrangência e diversidade das ações realizadas pelos serviços de APS.
Delphi Technique in the validation process of the national application of the Questionnaire for Primary Care Assessment (QualiAB)
Keywords: Quality of Health Care; Validation Studies; Delphi Technique; Peer Review; Primary Health Care; Qualidade da Assistência à Saúde; Estudos de Validação; Técnica Delfos; Revisão por Pares; Atenção Primária à Saúde